The language of graphic design an illustrated handbook for understanding fundamental design principles - Poulin, Richard (Rockport Publishers, 2011)
'The Language of Graphic Design' provides graphic design students and practitioners with an in-depth understanding of the fundamental elements and principles of their language, what they are, why they are important and how to use them effectively.